Methodology for the study of the traceability of runoff water feeding reservoirs - Ortega, LM; Ramos, MI; Enríquez, Carlos; Cubillas, Juan José (iwa publishing, 2024)
Water reservoirs are essential to ensure water supply to both the population and agriculture, especially in the Mediterranean basin. In some cases, analyses of water intended for human consumption have detected high levels of agrochemicals. Knowing the possible origin of these products is complex because there may be many agricultural plots within the reservoir basin. In this paper, we introduce a methodology to obtain the set of agricultural plots whose rainwater reaches the reservoir and in what proportion they affect the points where chemical analyses are performed. The method implements an extension of the D8 algorithm for the calculation of the drainage network, in which additional information about the land-use type of the area, as well as rainfall maps, are also considered. In order to facilitate the user's analysis of the data, a plugin has been implemented in QGIS. This allows usability and easy interaction with the visual information. The Rumblar reservoir basin, located in Andalusia (Spain) has been studied as a use case, surrounded by olive orchards. The result is a replicable methodology for any other water reservoir and for carrying out an individualized study of agricultural plots.
Keywords: D8 algorithm; olive orchards; QGIS plugin; rainfall maps; reservoir basin; water traceability